Pengaruh Environmental Performance dan Corporate Social Responsibility Disclosure Terhadap Kinerja Keuangan Pada Perusahaan Kosmetik di BEI - Windah Alfianah; Ryan Kurnia Rizkianto (Politeknik Ganesha Medan, 2023)
The purpose of this research is to test and analyze empirically influence environmental performance against the financial performance of cosmetics companies in indonesia and the influence of corporate social responsibility disclosure of financial performance cosmetics companies in Indonesia. This research use a quantitative approach. A subject in this research was cosmetics companies listed on the indonesia stock exchange period 2011-2018. Data presented in the form of descriptive statistics and produce 6 company and 36 samples. Research carried out by using multiple linear regression analysis environmental performance has a positive influence on the financial performance of corporations and CSR disclosure have a positive influence on financial performance shows that CSR is a form of transparent form of behavior and ethical was an image of corporate sustainbility .CSR can be used as a company to keep the company going concern sustainability in future.